2000
DOI: 10.1128/jvi.74.21.9964-9971.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cells Expressing the Epstein-Barr Virus Growth Program Are Present in and Restricted to the Naive B-Cell Subset of Healthy Tonsils

Abstract: In this paper we demonstrate, for the first time, that Epstein-Barr virus (EBV)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 42 publications
3
90
1
1
Order By: Relevance
“…We propose that viral reactivation results in de novo infection of a subset of IgD ϩ naive B cells, providing a mechanism for maintaining the longterm viral reservoir in wild-type mice. This possibility is supported by the observation that EBV infection of naive tonsillar B cells correlated with active viral replication in the tonsils (63). We hypothesize that memory B cell triggering fails to occur in SAPdeficient mice because of SAP-associated defects in B cell activation, resulting in the absence of virally infected naive B cells.…”
Section: Discussionmentioning
confidence: 76%
“…We propose that viral reactivation results in de novo infection of a subset of IgD ϩ naive B cells, providing a mechanism for maintaining the longterm viral reservoir in wild-type mice. This possibility is supported by the observation that EBV infection of naive tonsillar B cells correlated with active viral replication in the tonsils (63). We hypothesize that memory B cell triggering fails to occur in SAPdeficient mice because of SAP-associated defects in B cell activation, resulting in the absence of virally infected naive B cells.…”
Section: Discussionmentioning
confidence: 76%
“…RT-PCR was used to determine the expression of EBV genes indicative of viral replication and the three latency programs. The details of this assay have been published previously (7). Serial dilutions of isolated cell populations were prepared and aliquoted into Eppendorf tubes.…”
Section: Rt-pcrmentioning
confidence: 99%
“…This is evident from our previous studies in which we have shown that defined patterns of EBV gene expression are associated with specific populations of mature B cells. In the tonsils of healthy individuals, naive B cells, which are thought to be newly infected, express all nine known latency proteins (Epstein-Barr nuclear Ag 1 (EBNA1), 4 EBNA2, EBNA3a, EBNA3b, EBNA3c, and LP and latent membrane protein (LMP)1, LMP2a, and LMP2b) (7,8); infected germinal center and memory B cells express a limited set of three latency proteins (LMP1, LMP2a, and EBNA1(Q-K)) (8,9); and infected memory B cells in the blood cease expression of all viral proteins, with the exception that they express EBNA1 when they divide (4). Viral replication occurs in tonsillar plasma cells, resulting in expression of the lytic genes including BZLF1 (10).…”
mentioning
confidence: 99%
“…One of these programs, known as latency III or the "growth program," is characterized by the expression of a restricted set of approximately eight viral proteins, which activate B cells and drive their proliferation, thus increasing the viral reservoir. Latency III is found in EBV-associated malignancies in immunosuppressed patients (9) and likely reemerges continuously in healthy carriers (9,12), indicating that its control is critical for the health of an EBV carrier. Only at a later stage of infection (13) can the virus enter its lytic phase in infected cells to produce progeny virions, a phase requiring expression of the majority of viral proteins.…”
mentioning
confidence: 99%